DOI: 10.11606/t.22.2011.tde-31102011-084343
|View full text |Cite
|
Sign up to set email alerts
|

Logomúsica: a criação de um novo approach musicoterápico como veículo na promoção da saúde mental

Abstract: Esta pesquisa teve por objetivo a criação de um novo approach musicoterápico inspirado na logoterapia como veículo na promoção da saúde mental. Deste encontro e diálogo entre a logoterapia e as práticas musicoterápicas de base existencial-humanista e cultural, em um contexto de intervenção e pesquisa, nasceu a logomúsica, abordagem musicoterápica criada pelos pesquisadores. Foi montado um grupo de estudo com 15 usuários de um Centro Atenção Psicossocial ao longo de 10 meses de atuação e intervenção com encontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
4

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
(6 reference statements)
1
2
0
4
Order By: Relevance
“…These fi ndings suggest the applicability of Logotherapy in the promotion of actions of mental health and prevention of health problems in adolescence, as in similar work described by Bretones (1998), Leonardi (2011) andReinhold (2004). This study also presents some additional contributions to the initial study of Aquino et al (2011), among which, the replication in a new context, the use of multiple measures and the evaluation of the intervention process may be mentioned.…”
Section: Intervention For Promoting Meaning In Life In Adolescents: Esupporting
confidence: 72%
See 2 more Smart Citations
“…These fi ndings suggest the applicability of Logotherapy in the promotion of actions of mental health and prevention of health problems in adolescence, as in similar work described by Bretones (1998), Leonardi (2011) andReinhold (2004). This study also presents some additional contributions to the initial study of Aquino et al (2011), among which, the replication in a new context, the use of multiple measures and the evaluation of the intervention process may be mentioned.…”
Section: Intervention For Promoting Meaning In Life In Adolescents: Esupporting
confidence: 72%
“…The relationship between meaning in life, well-being and satisfaction with life has constituted the object of study in several investigations in Psychological Science Damásio, 2013;Gomes, 2009;Leonardi, 2011;Reinhold, 2004;Steger, 2009). Furthermore, studies have shown positive correlations between meaning in life and life satisfaction in adults between 22 and 60 years of age (Bonebright, Clay, & Ankenmann, 2000) and between the presence of meaning and subjective wellbeing in adults aged 18 to 88 years (Debats, Van der Lubbe & Vezeman, 1993;Doğana, Sapmaz, Telb, Sapmaz, & Temizel, 2012).…”
Section: Intervention For Promoting Meaning In Life In Adolescents: Ementioning
confidence: 99%
See 1 more Smart Citation
“…As relações entre sentido da vida, bem-estar e satisfação com a vida tem se constituído como objeto de estudo em diversas investigações na ciência psicológica Damásio, 2013;Gomes, 2009;Leonardi, 2011;Reinhold, 2004;Steger, 2009). Ademais, estudos têm demonstrado correlações positivas entre sentido da vida e satisfação com a vida em população adulta, entre 22 e 60 anos de idade (Bonebright, Clay, & Ankenmann, 2000) e entre presença de sentido e bem-estar subjetivo, em adultos de 18 a 88 anos (Debats, Van der Lubbe, & Vezeman, 1993;Doğana, Sapmaz, Telb, Sapmaz, & Temizel, 2012).…”
unclassified
“…São igualmente escassos na literatura nacional estudos de intervenções para promoção de sentido da vida em adolescentes. Além da proposta de Aquino et al (2011), foram encontrados apenas estudos em populações adultas, com resultados positivos para a promoção da autonomia e aumento da qualidade de vida de pacientes psicóticos (Leonardi, 2011) e prevenção do burnout em professores (Reinhold, 2004). Portanto, são ainda poucos os estudos nacionais com propósito de promoção de sentido da vida em fases iniciais do ciclo da vida em populações não clínicas.…”
unclassified